WORK PRODUCIVITY IN RHEUMATOID ARTHRITIS: ANALYSIS FROM MULTICENTER TURKISH STUDY - Pamuk, O. N.; Cetin, P.; Solmaz, D.; Ertenli, I.; Akar, S.; Karaaslan, Y.; Akkoc, N. (Bmj Publishing Group, 2015)
[Abstract Not Available]